THE THEME OF THE “RUSSIAN WORLD” IN THE MONUMENTS OF THE TIME OF TROUBLES (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-135-150DOI 10.18522/1995-0640-2024-1-135-150Эпоха Смутного времени повлияла на особый характер литературы и обострила тему «русского мира», которая к XVI в. стала устойчивой. В двух публицистических памятниках – «Новой повести о преславном Российском царстве» и «Плаче о пленении и о конечном разорении Московского государства» – находят отражение волнующие авторов вопросы о текущем положении Руси: отсутствие законного правителя, польско-шведская интервенция, возможность восхождения на престол чужеземца. Эти вопросы оказываются связанными и с темой «русского мира», которая рассматривается сквозь призму авторских призывов не допустить разрушения основ, составляющих русский цивилизационный код.Ключевые слова: русский мир, Смутное время, цивилизационный код, православие, правительБлагодарности: Публикация подготовлена в рамках реализации ГЗ ЮНЦ РАН, № гр. проекта 122020100347-2.The era of the Time of Troubles influenced the special character of literature and exacerbated the theme of the “Russian worldˮ, which by the XVI century had become stable. Two journalistic monuments ‘The New Tale of the Glorious Russian Kingdom’ and ‘The Lament of the Captivity and the Final Ruin of the Moscow state’ reflect the authors' concerns about the current situation of Russia: the absence of a legitimate ruler, the Polish-Swedish intervention, the possibility of ascension to the throne of a foreigner. The theme of the “Russian worldˮ, which is viewed through the prism of the author's calls not to allow the destruction of the foundations that make up the Russian civilizational code, also turns out to be related to these issues.Key words: Russian world, the Time of the Troubles, civilizational code, Orthodox Christianity, governorAcknowledgments: The publication was prepared as part of the implementation of the SO of the Southern Scientific Center of the Russian Academy of Sciences, project no. 122020100347-2.